At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the equation [tex]\( |5x - 3| = |x + 7| \)[/tex] step-by-step.
First, recall that for any two real numbers [tex]\(a\)[/tex] and [tex]\(b\)[/tex], [tex]\( |a| = |b| \)[/tex] implies that either [tex]\(a = b\)[/tex] or [tex]\(a = -b\)[/tex]. We will apply this property to solve the given equation.
### Case 1: [tex]\( 5x - 3 = x + 7 \)[/tex]
1. Start by setting the expressions inside the absolute values equal to each other:
[tex]\[ 5x - 3 = x + 7 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
[tex]\[ 5x - 3 = x + 7 \][/tex]
Subtract [tex]\(x\)[/tex] from both sides:
[tex]\[ 4x - 3 = 7 \][/tex]
Add 3 to both sides:
[tex]\[ 4x = 10 \][/tex]
Divide both sides by 4:
[tex]\[ x = \frac{10}{4} = \frac{5}{2} \][/tex]
### Case 2: [tex]\( 5x - 3 = -(x + 7) \)[/tex]
1. Set the expression inside the first absolute value equal to the negation of the expression inside the second absolute value:
[tex]\[ 5x - 3 = -(x + 7) \][/tex]
2. Simplify the right-hand side:
[tex]\[ 5x - 3 = -x - 7 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ 5x - 3 = -x - 7 \][/tex]
Add [tex]\(x\)[/tex] to both sides:
[tex]\[ 6x - 3 = -7 \][/tex]
Add 3 to both sides:
[tex]\[ 6x = -4 \][/tex]
Divide both sides by 6:
[tex]\[ x = \frac{-4}{6} = \frac{-2}{3} \][/tex]
### Conclusion
The solutions to the equation [tex]\( |5x - 3| = |x + 7| \)[/tex] are:
[tex]\[ x = \frac{5}{2} \quad \text{and} \quad x = \frac{-2}{3} \][/tex]
First, recall that for any two real numbers [tex]\(a\)[/tex] and [tex]\(b\)[/tex], [tex]\( |a| = |b| \)[/tex] implies that either [tex]\(a = b\)[/tex] or [tex]\(a = -b\)[/tex]. We will apply this property to solve the given equation.
### Case 1: [tex]\( 5x - 3 = x + 7 \)[/tex]
1. Start by setting the expressions inside the absolute values equal to each other:
[tex]\[ 5x - 3 = x + 7 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
[tex]\[ 5x - 3 = x + 7 \][/tex]
Subtract [tex]\(x\)[/tex] from both sides:
[tex]\[ 4x - 3 = 7 \][/tex]
Add 3 to both sides:
[tex]\[ 4x = 10 \][/tex]
Divide both sides by 4:
[tex]\[ x = \frac{10}{4} = \frac{5}{2} \][/tex]
### Case 2: [tex]\( 5x - 3 = -(x + 7) \)[/tex]
1. Set the expression inside the first absolute value equal to the negation of the expression inside the second absolute value:
[tex]\[ 5x - 3 = -(x + 7) \][/tex]
2. Simplify the right-hand side:
[tex]\[ 5x - 3 = -x - 7 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ 5x - 3 = -x - 7 \][/tex]
Add [tex]\(x\)[/tex] to both sides:
[tex]\[ 6x - 3 = -7 \][/tex]
Add 3 to both sides:
[tex]\[ 6x = -4 \][/tex]
Divide both sides by 6:
[tex]\[ x = \frac{-4}{6} = \frac{-2}{3} \][/tex]
### Conclusion
The solutions to the equation [tex]\( |5x - 3| = |x + 7| \)[/tex] are:
[tex]\[ x = \frac{5}{2} \quad \text{and} \quad x = \frac{-2}{3} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.